Propulsion efficiency in wheelchair tennis: a case study on the influence of the racket on the handrim forces - Vitor Alcolea; Guilherme da Silva Bertolaccini; Rubens Venditti Junior; Fausto Orsi Medola (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: to evaluate how the act of holding a tennis racket influences the application of forces in the handrim during manual wheelchair propulsion at a self-selected comfortable speed and sprint. Methods: A case study was conducted with an experienced wheelchair tennis player who propelled the wheelchair in a straightforward trajectory at two different velocities (self-selected comfortable speed and sprint) in two different conditions (freehand and holding the racket). Kinetic and temporal data of the pushes were obtained with the SmartWheel system attached in substitution to the conventional rear wheel at the dominant side of the player. Results: holding the racket affects the propulsion pattern mainly when an accelerated movement is required (sprint). Compared to the propulsion at a self-selected speed, propelling the chair as fast as possible with the racket in hands resulted in lower total and tangential forces on the handrim, and decreased push time and increased push frequency. Conclusion: Such influence on both kinetic and temporal propulsion impact the mechanical efficiency of the manual wheelchair propulsion, which may, ultimately, affect the sport´s performance. Special attention should be directed to the propulsion training with the racket in maneuvers and motions that are characteristic of the wheelchair tennis match in an attempt to provide the athlete with proper technique for optimal propulsion efficiency and sports performance.